Manufacture of tetracaine hydrochloride lozenges preparation by direct compression and wet granulation methods - Gazikalović Emilija; Obrenović Dušan; Nidžović Živorad; Čolić Olivera (Vojnosanitetski Pregled)
The results of quality testing of lozenges made by direct compression and by wet granulation procedure (Ph. Jug. IV) are presented. The aim was to determine hardness, friability and disintegration of the lozenges. Considering the fact that the produced tetracaine hydrochloride lozenges were not transported, but were made according to the needs of the Clinic of Gastroenterology, Military Medical Academy, time of disintegration, not hardness and friability, was the priority in making a choice of formulation. That is why tetracaine hydrochloride lozenges made with 3.5% solution of carmellose sodium, which have the longest disintegration were chosen, which made possible the longest contact of the local anesthetic with mucous membrane of mouth and throat.